Hybrid materials of pyrene substituted phthalocyanines with single-walled carbon nanotubes: structure and sensing properties - Kaya, Esra Nur; Basova, Tamara; Polyakov, Maxim; Durmuş, Mahmut; Kadem, Burak; Hassan, Aseel (Royal Soc Chemistry, 2015)
Hybrid materials of single walled carbon nanotubes (SWCNT) were obtained by their non-covalent functionalization with asymmetrically polyoxyethylene substituted phthalocyanines (MPc-py (M = Cu, Co, 2H)) bearing one pyrene group as a substituent. The attachment of MPc-py molecules onto the SWCNT surface have been confirmed using Raman spectroscopy, SEM, TEM and thermogravimetric analysis. The pyrene substituents were introduced to the phthalocyanine macrocycle in order to improve pi-pi interaction between the MPc-py and SWCNT. The effect of the central metal on the formation and sensor properties of the MPc-py within the hybrids has been verified. It has been shown that the electrical response of the hybrid films to ammonia vapor in the concentration range of 10-50 ppm changes in the following order CuPc-py > CoPc-py > H2Pc-py, which was found to be in good correlation with the amount of phthalocyanine molecules adsorbed onto the SWCNT walls, as estimated by thermogravimetric analysis (TGA).
Keywords: Metal-Free Phthalocyanine; Covalent Functionalization; Zinc Phthalocyanine; Thin-Films; Sensor; Copper; Nickel; Nh3; Sensitivity; Performance